2010
DOI: 10.1080/00222341003648995
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Effects of a Novel Nucleating Agent Bicyclic [2,2,1] Heptane Di-carboxylate in Isotactic Polypropylene

Abstract: Nucleation effects of a novel nucleating agent, bicyclic [2,2,1] heptane di-carboxylate (commercial product name: , in isotactic polypropylene (iPP) were studied by using differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WAXD). The results showed that HPN-68 is a typical nucleating agent for α-iPP and has high nucleation efficiency. Crystallization peak temperature and mechanical properties of iPP nucleated with HPN-68 can be greatly increased with only a low concentration of HPN-68. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…So far, to the best of our showed excellent nucleation efficiency in iPP at very low addition amount (e.g., 0.20wt%). When the addition amount of Hyperform HPN-20E in iPP was 0.20wt%, compared to those of pure iPP, the tensile strength, tensile modulus, flexural strength and flexural modulus were increased by 10.81%, 8.65%, 16.67% and 11.96%, respectively, which was comparable to the effect on mechanical properties of a highly effective commercial nucleating agent, Hyperform HPN-68 [30], indicating that Hyperform HPN-20E was highly effective for iPP. When the addition amount of Hyperform HPN-20E in iPP was low, it was difficult for the nucleating agent particles incorporated into the iPP to agglomerate together and all particles played the role of nuclei.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…So far, to the best of our showed excellent nucleation efficiency in iPP at very low addition amount (e.g., 0.20wt%). When the addition amount of Hyperform HPN-20E in iPP was 0.20wt%, compared to those of pure iPP, the tensile strength, tensile modulus, flexural strength and flexural modulus were increased by 10.81%, 8.65%, 16.67% and 11.96%, respectively, which was comparable to the effect on mechanical properties of a highly effective commercial nucleating agent, Hyperform HPN-68 [30], indicating that Hyperform HPN-20E was highly effective for iPP. When the addition amount of Hyperform HPN-20E in iPP was low, it was difficult for the nucleating agent particles incorporated into the iPP to agglomerate together and all particles played the role of nuclei.…”
Section: Introductionsupporting
confidence: 78%
“…0.15wt%. When the amount of Hyperform HPN-20E in iPP was 0.2wt%, compared to that of pure iPP, the haze value of iPP was decreased by 42.44%, which was better than that of iPP nucleated with Hyperform HPN-68 [30]. The addition of the nucleating agent into iPP presumably reduced the spherulite size of iPP, resulting in improved transparency of iPP as the haze value was decreased greatly.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…It has been comprehensively shown that the addition of nucleating agents can affect the crystallisation of a semi‐crystalline polymer like iPP. Structural polymorphism of iPP exists within its crystalline domain; among the crystalline polymorphs present, the β ‐crystalline phase has been shown to contribute to properties such as increased elongation at break, improved ductility and higher impact strength . The β ‐polymorph phase may be induced in iPP by the use of β ‐nucleating agents ( β ‐NAs), but will never inhibit the formation of the more commonly found phase ( α ‐polymorph) .…”
Section: Introductionmentioning
confidence: 99%
“…The properties of crystalline polymers are determined by their structure which can be modified by two main approaches: i) to control molecular structure and increase chain regularity 6,7 or ii) to use nucleating agents [8][9][10][11][12][13][14] . Modern polymerization and catalyst technology reached very high levels, further progress is difficult.…”
Section: Introductionmentioning
confidence: 99%